Estimation Heterosis and Combining Ability for Yield and Yield Contributing Traits in Two -Rowed Barley Using Line X Tester - Mustafa, Kamil Mahmood (Sulaimani Journal for Pure and Applied Sciences, 2018)
Five diverse genotypes of tow-rowed barley were crossed with a line × tester fashion. Combining ability for grain yield and yield related in tow-rowed barley was investigated in a set of two female lines, three male testers and their six F1’s hybrids. Analysis of variance detected highly significant differences for all of the quantitative traits studied among the genotypes, among the parents for GCA, among the crosses for SCA, while most traits among Parents x crosses and among Lines x Testers. The parent GOB (line) had a positive and significant effect for grain yield plant-1 only. Two crosses were found to be well enough specific combiners for grain yield plant-1 with maximum SCA effect in cross GOB x MSEL. The estimated value of σ2A was greater than its σ2D for grains spike-1, thousand grain weight and plant height, which pointed out the predominance of additive gene action as the ratio of σ2A/σ2D was more than unity, whereas the rest of the traits viz., spike plant-1, spike length, harvest index biological yield plant-1 and grain yield plant-1 appeared overbalance of non-additive gene action. The average degree of dominance values for spike length and 1000- grain weight indicated partial dominance while rest of the traits showed over-dominance. All the crosses, excluding CANELA x MSEL, showed good positive and significant heterosis for grain yield plant-.
Keywords: Barley; GCA; SCA; Heterosis; Yield component; Gene effects